Effectiveness Test of Tome-tome Fruit Ethanol Extract (Flacourtia inermis,Roxb) against Antidiabetes in White Rats (Rattus norvegicus) Induced by Alloxan - Fricilia Leony Mey Jacob; Meity Neltje Tanor; Nonny Manampiring (Indonesian Biodiversity Journal, 2021)
Diabetes mellitus is a chronic metabolic syndrome disorder of carbohydrates, lipids, and fats caused by insulin deficiency in the body causing blood glucose above the normal threshold (hyperglycemia). Tome-tome (Flacourtia inermis, Roxb) contains anthocyanins which have the ability to lower blood sugar levels. This study aimed to determine the effectiveness of the ethanolic extract of tome-tome fruit (Flacourtia inermis, Roxb) and to see what dose and day treatment was most effective against diabetes in white rats (Rattus norvegicus) induced by alloxan. The place of research was carried out at the Pharmacy Laboratory of Trinita University, Manado with a research time of 3 months. The test animals used were 25 white rats (Rattus norvegicus) divided into 5 treatment groups, namely normal control, negative control, positive control (glibenclamide) and ethanol extract of tome-tome fruit with doses of 150 mg/kgBW and 300 mg/kgBW. Blood glucose measurements were carried out on day 1, day 7, and day 14. The results showed that the effectiveness of tome-tome fruit ethanol extract against alloxan-induced diabetic rats decreased blood glucose levels. A dose of 150 mg/kgBW ethanol extract of tome-tome fruit was more effective in reducing blood glucose levels compared to a dose of 300 mg/kgBW rats.